2010
DOI: 10.1093/eurpub/ckq035
|View full text |Cite
|
Sign up to set email alerts
|

Sedentary behaviours and socio-economic status in Spanish adolescents: the AVENA study

Abstract: Spanish adolescents presented different sedentary patterns according to age, gender and SES. Boys reported more time engaged in electronic games, whereas girls reported more time studying. Parental occupation had more influence than parental education on the time spent in sedentary behaviours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
1
12

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 32 publications
5
42
1
12
Order By: Relevance
“…Adolescents of low economic level showed longer screen time in a study developed in EUA 28 and Europe 6 . This study is also consistent with review developed by Pate et al 7 , who reported longer screen time for adolescents of lower economic class.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Adolescents of low economic level showed longer screen time in a study developed in EUA 28 and Europe 6 . This study is also consistent with review developed by Pate et al 7 , who reported longer screen time for adolescents of lower economic class.…”
Section: Discussionmentioning
confidence: 94%
“…For example, in a study of European adolescents, the time sitting in front of the TV was higher in adolescents with worse socioeconomic indicators. However, the time sitting in front of PC and VG was higher in those of better socioeconomic indicators 6,14 .…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations